CHOOSING A PROFESSION AS A MODELING OF THE YOUTH FUTURE (BASED ON SOCIOLOGICAL RESEARCH) - Skosyreva, Nina; Razumov, Vladimir; Zinich, Alla; Pomogaev, Vitalii; Revyakina, Yulia; Gefner, Olga (Revista Gênero e Interdisciplinaridade, 2020)
The most important resource in forming human capital is, certainly, the youth, whose mission is not just to reproduce, but also to develop, improve, and update the existing social system. In the article authors are trying to find answers to the following questions: How do contemporary youth see their future? How does this image correlate with the socio-economic challenges facing contemporary society? What help do young people need in the course of professional self-determination? The answers to these questions should be taken into account when developing strategies for the effective use of the human capital of today’s youth. Based on the results obtained, the authors conclude that it is necessary to typologize behavioral strategy models in the future professional self-determination of young people.